The multi-objective optimization for urban drainage rehabilitation - Cordero, Wilmer Jose Barreto (Leiden : CRC Press, 2012)
Introduction--Urban Drainage Rehabilitation--A Multi-tier Framework for Urban Drainage Rehabilitation--Multi-Objective Optimization--Multi-Objective Optimization in UDS Rehabilitation--Parallel Computing in Optimization of Large-Scale Systems--Framework Application in Delevoping Cities--Conclusion and Recommendations